2023
DOI: 10.3389/fvets.2023.1154625
|View full text |Cite
|
Sign up to set email alerts
|

A recent distemper virus outbreak in the growing canine populations of Galapagos Islands: a persistent threat for the endangered Galapagos Sea Lion

Abstract: Canine Distemper Virus (CDV) is a highly contagious virus that can cross mammalian species barriers and has widespread impacts on both domestic animals and wildlife populations. This study describes a recent outbreak of CDV in the Galapagos Islands in 2019. A total number of 125 dogs with clinical signs compatible with CDV were included in this study. Nasal swabs were taken and analyzed by RT-qPCR for the detection of CDV, resulting in a positivity rate of 74.4% (IC95%, 66–81%). Among the CDV positive dogs, 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…CD is an endemic disease, and numerous outbreaks have been documented across various regions globally [31]. In 2023, CD outbreaks were found in Galapagos Islands threatening the endangered Galapagos Sea Lion [32], in captive tigers in Thailand [33], and in Palm civets in India [34]. Recently, CDV was also detected in wild carnivores in multiple European countries, such as Italy, Hungary, Spain, Croatia, and Germany [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…CD is an endemic disease, and numerous outbreaks have been documented across various regions globally [31]. In 2023, CD outbreaks were found in Galapagos Islands threatening the endangered Galapagos Sea Lion [32], in captive tigers in Thailand [33], and in Palm civets in India [34]. Recently, CDV was also detected in wild carnivores in multiple European countries, such as Italy, Hungary, Spain, Croatia, and Germany [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The last assessment reported that the human/dog ratio was 4.04:1, representing an increase of 55% in the dog population on Santa Cruz Island from 2014 to 2018 [8,10]. This growing canine population can increase the risk of transmission of infectious diseases, such as that caused by the canine distemper virus (CDV), which could severely affect endangered species such as the GSL [11,12]. In turn, parasitic diseases such as heartworm (Dirofilaria immitis) disease and bacterial infections caused by Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple reports of CDV circulation in dogs in the Galapagos Islands were published, indicating that the serological prevalence increased from 22% in 2004 [23] to 36% in 2014 [10], with well-documented outbreaks of CDV killing more than 600 dogs on Santa Cruz and Isabela islands in the early 2000s [10,23]. Recently, a study conducted on Santa Cruz Island reported a total of 125 dogs with clinical signs compatible with CDV infection, with 74.4% (IC95%, 66-81%) of the animals found positive by RT-qPCR for CDV detection [12]. This motivated vaccination campaigns for domestic dogs in the archipelago [12]; however, virus spread at dog-wildlife interfaces is generally not controlled [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations